2010
DOI: 10.1038/jp.2010.121
|View full text |Cite
|
Sign up to set email alerts
|

Who is performing medical procedures in the neonatal intensive care unit?

Abstract: Objective: Owing to resident work-hour reductions and more permanent personnel in the newborn intensive care unit (NICU), we sought to determine if pediatric housestaff are missing learning opportunities in procedural training due to non-participation.Study Design: A prospective, observational study was conducted at an academic NICU using self-reported data from neonatal personnel after attempting 188 procedures on 109 neonates, and analyzed using Fisher's exact and w 2 -tests.Result: Housestaff first attempte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 12 publications
(19 reference statements)
0
37
0
Order By: Relevance
“…30 neonatal intubations throughout residency training in 1994-1996 and that number had declined to , 20 in 1999-2002. Gozzo et al, 8 examining whether residents missed procedural opportunities because of nonparticipation, found a significantly smaller percentage of procedures attempted by residents (32%) compared with nonresident practitioners. Decreasing procedural opportunities have been attributed to duty hour restrictions, limited intensive care rotations, and the presence of increasing numbers of other clinical personnel, such as nurse practitioners, physician assistants, fellows, and attending hospitalists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 neonatal intubations throughout residency training in 1994-1996 and that number had declined to , 20 in 1999-2002. Gozzo et al, 8 examining whether residents missed procedural opportunities because of nonparticipation, found a significantly smaller percentage of procedures attempted by residents (32%) compared with nonresident practitioners. Decreasing procedural opportunities have been attributed to duty hour restrictions, limited intensive care rotations, and the presence of increasing numbers of other clinical personnel, such as nurse practitioners, physician assistants, fellows, and attending hospitalists.…”
Section: Discussionmentioning
confidence: 99%
“…Residents' lack of procedural competence may, in part, be a reflection of limited clinical opportunities to perform procedures 6,8 and/or inadequate alternative procedural education. A 2007 article 4 noted that only 40% to 70% of pediatrics residency programs have a formal method for teaching arterial puncture, bladder catheterization, peripheral IV placement, lumbar puncture, and venipuncture.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric residents' suboptimal success rates likely stem from the limited experience with neonatal intubation. Gozzo et al observed that pediatric residents performed few procedures in the NICU [9]. In a 2015 study of pediatric resident neonatal intubation competency, DeMeo et al cited a median number of 3 intubation opportunities per resident during training [10].…”
Section: Neonatal Intubation Success Rates and Complicationsmentioning
confidence: 99%
“…In a 2015 study of pediatric resident neonatal intubation competency, DeMeo et al cited a median number of 3 intubation opportunities per resident during training [10]. The limited clinical experience is multifactorial, resulting from restrictions in duty hours and NICU rotations [11], increased presence of advanced practice providers in the NICU [9,12], changes in management of infants with meconium-stained amniotic fluid [13], and increasing usage of non-invasive ventilation strategies [14]. As opposed to residents, neonatal fellows report considerably more neonatal intubation experiences, with an average of 60 intubations by graduation [15].…”
Section: Neonatal Intubation Success Rates and Complicationsmentioning
confidence: 99%
“…In fact, other studies have used the starting point of describing current processes for intubation and their overall success, including provider, patient, and procedural characteristics, concluding that success can fluctuate widely [15]. Due to this finding, some potential solutions suggested for advancing procedural education include specific critical care tracks to increase procedural exposure, the use of smartphone technology, optimizing procedural exposure of house staff, and simulation, including “just in time” training and deliberate practice, especially in light of overall decreasing attendance at deliveries during training periods [2, 15-18]. These approaches would likely compliment the “5 Ps” and provide meaningful input from both the trainer and the trainee.…”
mentioning
confidence: 99%